2022
DOI: 10.1155/2022/9536617
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Changes of Liver and Kidney Function-Related Indicators and Clinical Significance in Patients with OSAHS

Abstract: Purpose. To study the changes of liver and kidney function-related indexes in patients with obstructive sleep apnea hypopnea syndrome (OSAHS) and analyze their clinical significance. Method. Ninety OSAHS patients treated in our hospital from April 2019 to April 2021 were selected. According to the apnea-hypopnea Index (AHI), they were divided into mild OSAHS group (5 ≤ AHI < 15 times/h, 35 people), moderate OSAHS group (15 ≤ AHI < 30 times/h, 35 people), and severe OSAHS group (AHI ≥ 30 times/h, 20 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%